Introduction to general, organic, and biochemistry - Hein, Morris (John Wiley & Sons, 2005)
Offers a foundation for a future career in allied health or nursing - a foundation built on fundamental principles and solid problem-solving skills. This book provides a variety of exercises, including practice exercises and end-of-chapter exercises, as well as challenge exercises and worked examples.